2016
DOI: 10.1111/ijcs.12309
|View full text |Cite
|
Sign up to set email alerts
|

Environmental factors of food literacy in Australian high schools: views of home economics teachers

Abstract: This study set out to examine environmental factors impacting on the food literacy of adolescents. It utilized data from a nation‐wide survey of home economics teachers regarding their experience of food literacy education in Australian high schools. Content analysis and the ANGELO framework were applied to analyse free‐text comments from 78 of the respondents that were collected as part of a more extensive data set. The analysis of environmental factors revealed three enablers and ten barriers that could infl… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
59
0
1

Year Published

2018
2018
2024
2024

Publication Types

Select...
5
2

Relationship

1
6

Authors

Journals

citations
Cited by 41 publications
(63 citation statements)
references
References 33 publications
3
59
0
1
Order By: Relevance
“…Moreover, they also addressed disadvantaged young individuals [37,56,61]. In line with the authors that focused on NL, these researchers which discussed FL considered some social factors that affected FL: socioeconomic level [3,38,56,57,62], education, and literacy [3,23,56,[62][63][64][65].…”
Section: Antecedents Of Flmentioning
confidence: 95%
See 2 more Smart Citations
“…Moreover, they also addressed disadvantaged young individuals [37,56,61]. In line with the authors that focused on NL, these researchers which discussed FL considered some social factors that affected FL: socioeconomic level [3,38,56,57,62], education, and literacy [3,23,56,[62][63][64][65].…”
Section: Antecedents Of Flmentioning
confidence: 95%
“…On the one hand, Ronto et al [62] indicated that the school curriculum could play a vital role in enhancing FL in adolescents. Furthermore, the authors of six papers emphasized the importance of teaching home economics [24,62,64,65], the vital role of academic food literacy programs [66], and the priority of school to impart food knowledge and competences [67]. On the other hand, Ronto et al [24,64,65] emphasized the economic and human resources necessary to impart such knowledge and competences to younger people.…”
Section: Antecedents Of Flmentioning
confidence: 99%
See 1 more Smart Citation
“…Finally, while not a limitation per se, it is important to see food literacy for what it is intended, i.e., a form of literacy : the outcome of educational goals intended to inform, develop personal skills and contribute to personal and community empowerment, and social change (Nutbeam, ). Where food literacy will fail as an emancipatory health promotion tool is when it is decontextualized from unjust societal processes such as social and health inequity, and unhealthy food environments (Ronto et al, ). As Doris Gillis states, valourizing food literacy as THE determinant of food choice separates people from their environments, and reinforces the ideology of individual responsibility for health behaviours, and therefore health outcomes (Gillis, , p. 94).…”
Section: Discussionmentioning
confidence: 99%
“…This is important to ensure that food literacy, as a critical heal promotion tool, is evidence-based and does not take on a "moralistic" dimension whereby it is imbued with inherent qualities that are not empirically supported (Bowen, Elliott, & Brenton, 2014;Coveney, Begley, & Gallegos, 2012 (Nutbeam, 2000). Where food literacy will fail as an emancipatory health promotion tool is when it is decontextualized from unjust societal processes such as social and health inequity, and unhealthy food environments (Ronto et al, 2017a). As Doris Gillis states, valourizing food literacy as THE determinant of food choice separates people from their environments, and reinforces the ideology of individual responsibility for health behaviours, and therefore health outcomes (Gillis, 2016, p. 94).…”
Section: Framework: Food Literacy Competencies For Young Adultsmentioning
confidence: 99%